PROFITABILTAS MEMODERASI LIKUIDITAS DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN - Retnasari, Ati; Setiyowati, Supami Wahyu; Irianto, Mochamad Fariz (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aims to determine whether provitability is able to moderate the relationship of liquidity and growth to the value of the company. The value of the company is a value that reflects the credibility of the company in the eyes of the public, especially investors and prospective investors. The sample of this research is 58. This study uses multiple analyst regressions in the data analyst. The results showed that liquidity and growth had a negative effect on firm value. Profitability moderates the relationship of liquidity and growth to the value of the company.